2013
DOI: 10.1111/acem.12148
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Ultrasound‐assisted Examination of Skin and Soft Tissue Infections in the Pediatric Emergency Department

Abstract: Objectives To evaluate the test characteristics of clinical examination (CE) with the addition of bedside emergency ultrasound (CE+EUS) compared to CE alone in determining skin and soft tissue infections (SSTIs) that require drainage in pediatric patients. Methods This was a prospective study of CE+EUS as a diagnostic test for the evaluation of patients 2 months to 19 years of age evaluated for SSTIs in a pediatric emergency department (ED). Two physicians clinically and independently evaluated each lesion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 35 publications
0
69
0
1
Order By: Relevance
“…A third study demonstrated that POCUS did not improve upon the already optimal test characteristics of clinical examination alone when physicians were certain of their diagnosis; however, POCUS may be of use in cases of clinical uncertainty [310]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…A third study demonstrated that POCUS did not improve upon the already optimal test characteristics of clinical examination alone when physicians were certain of their diagnosis; however, POCUS may be of use in cases of clinical uncertainty [310]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…Both radiopaque and radiolucent foreign bodies appear hyperechoic on ultrasound, often with posterior acoustic shadowing which may assist in the detection of the foreign body [306310]. Other sonographic findings include reverberation (or “comet tails”) artifact, and a hypoechoic halo.…”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…20,26,[46][47][48] Point-of-care US in pediatric patients by PEM providers has recently been adopted into practice, and the literature is still evolving. Nonetheless, there are numerous studies demonstrating the accuracy of point-of-care US by PEM physicians [49][50][51][52][53][54][55][56][57][58] and the ability of PEM physicians to become proficient in point-of-care US after adequate training. 55,56,59 Although the point-ofcare US examinations performed should be specific to the needs of the department, the most common indications for which point-of-care US is being used in PEM are for focused assessment with sonography in trauma, soft tissue evaluation, and vascular access.…”
Section: Diagnostic and Procedural Indicationsmentioning
confidence: 99%
“…L'échographie a modifié la prise en charge de 13 à 22 % des patients. La faisabilité, après une formation courte, par des pédiatres urgentistes a été démon-trée [36].…”
Section: Spécificité Pédiatriqueunclassified